Risk Factors of Community Acquired Pneumonia among Under Five Children in a Tertiary Level Hospital in Rajshahi (TAJ: Journal of Teachers Association, 2023)
Introduction: Community acquired pneumonia (CAP) top the list of causes of under five children mortality in the world. Proper assessment of these risk factors and controlling them may help decrease the morbidity and mortality in under-five children suffering from CAP in Bangladesh and thereby help in improving the quality of life of our future generation.Objective: To assess the risk factors of CAP  among  under  five children  ( 2-59 months )  in a  tertiary  level hospital in Rajshahi.Materials and methods: This is a case control study which was carried out in the department of Pediatrics and EPI center of Rajshahi Medical College Hospital, RMCH from January 2017 to December 2018 to determine the risk factors of CAP among under five children. For this study, total 246 children, aged 2 months to 59 months, were selected   by purposive sampling technique. 123 were cases who were taken from indoor and 123 were healthy controls who were taken from out patients department & EPI centre. After taking written consent from guardians, history was taken and physical examination was done. All informations were recorded in a predesigned data sheet. Chi-square test and odds ratio were used to demonstrate level of significance.Results: Among 246 children greater number of patients of both group were male and came from rural area. Cases were predominant under 12 months and came from lower socioechonomic status. A statistically significant association was found between social class and CAP (